1988
DOI: 10.1002/jhet.5570250414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactions of some 6‐(2‐hydroxy‐1‐naphthyl)‐1,2,4‐triazines

Abstract: 4,5‐Benzocoumaran‐2,3‐dione condenses with semicarbazide and thiosemicarbazide at the 3‐position and the products obtained were converted to the corresponding 6‐(2‐hydroxy‐1‐naphthyl)‐1,2,4‐triazines. Reactions of these triazines with some reagents are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…To date, only a few studies have investigated the synthesis of benzofurotriazine derivatives. In 1988, Eid et al reported the synthesis of naphthofuro[2,3- e ][1,2,4]triazine in a 33% overall yield via the annulation of the triazine core to naphthofuran-1,2-dione [ 51 ]. The reaction was carried out in four steps.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have investigated the synthesis of benzofurotriazine derivatives. In 1988, Eid et al reported the synthesis of naphthofuro[2,3- e ][1,2,4]triazine in a 33% overall yield via the annulation of the triazine core to naphthofuran-1,2-dione [ 51 ]. The reaction was carried out in four steps.…”
Section: Introductionmentioning
confidence: 99%